Técnica de tratamiento faciales y su influencia en el aprendizaje de belleza a Estudiantes del Centro de Formación Artesanal Particular cinco de noviembre del Cantón Naranjal, Provincia Guayas. - Rivera Campoverde, Egda Cecilia (2017)
The techniques of facial treatments is a set of techniques and means that are used to improve the care of the skin of the face. The skin of each person is different and, therefore, requires different care: tailored to each skin. Therefore, know how to give a good facial diagnosis is essential to know the particularities of the skin of each one and thus choose the ideal treatment to treat the problems and specific needs detected. They are a series of specialized procedures that consist of performing treatments made with chemical or natural bases that help to improve the imperfections of the delicate skin of the face. The impurities, pollution and the own fat that our skin generates can end up clogging our pores and preventing our skin from breathing properly. So that this does not happen, we must bear in mind the importance of having a good facial cleansing and take it as a habit in the day to day. This means that by defining these two words treatment means that it is a set of means that are used to have a smooth skin. The term is a set of elements or means used to improve the care of the skin of the face.